“TEACH ME HOW TO CURSE MY ENEMIES”: POLITICAL WOMEN AND THEATRICAL POWER IN SHAKESPEARE’S FIRST TETRALOGY - Moore, Elizabeth (My University, 2012)
Drawing on Katherine Eggert’s discussion of Joan la Pucelle’s dramatic skills, this thesis argues that, through effective performances on the characters around them, the women of Shakespeare’s first tetralogy achieve and exercise extensive political power and that the male project of silencing these women through vilification and condemnation is an attempt to diminish that political power. The women in these plays are not born to the power they achieve, and it is not bestowed upon them by others. The female characters of the first tetralogy use theatrical power to enter and, in some cases, dominate the masculine world of political authority through their theatrical skill. They persuade, seduce, manipulate, and argue their ways through the highest circles of political authority and, transgressing patriarchal notions of political authority, they wield decidedly unfeminine power.
These plays demonstrate the potential public impact and rebellious or resistant power of the female voice. In the first chapter of this thesis, I argue that these characters, through dramatically effective speech, exert significant female political agency. In the second chapter, I further contend that the male project of silencing these women's voices, expressed through gendered slurs and accusations of sexual misconduct, is a method of subduing the women’s political power. By examining the subversive women of Shakespeare's first tetralogy, this thesis explores the ways in which these characters use voice to enter and, in some cases, dominate the masculine world of political authority.
Keywords: Henry VI; Richard III; Margaret of Anjou; Joan la Pucelle; history play; Literature in English, British Isles; Literature in English, British Isles